OCVPSS (Online Check Village Payment Supporting System) in the Realization of PBB Revenue in All Villages in Banyuwangi - A.A. Gde Satia Utama; Deddy Kurniawansyah; Panji Kusuma Prasetyanto; Pending Puji Dwi Astuti; Yashinta Setyowati; Romzi Kharisanto; Eka Elmi Hikmawati (AIBPM Publisher, 2019)
BAPENDA (Badan Pendapatan Daerah) is one of the entity in Banyuwangi to collect payment as Land and Property Tax (Pajak Bumi dan Bangunan–PBB) and Acquisition of Land and Property Rights (Bea Perolehan Hak atas Tanah dan Bangunan–BPHTB). Information systems in PBB-P2 collection using the application of Sistem Manajemen Informasi Objek Pajak (SISMIOP). SISMIOP is used to facilitate tax oversight and tax collection. However, the system still has weaknesses, has not been able to provide accurate reporting of acceptance data every time to stakeholders, especially villages in Banyuwangi. This study aims to create SISMIOP supporting system to increase interaction between BAPENDA and all village. Data were analyzed by exploratory descriptive method and content analysis. The result of this research is information system which suitable with BAPENDA and Village characteristic that is OCVPSS (Online Check Village Payment Supporting System) Realization of PBB Revenue. The next action is to apply OCVPSS to BAPENDA and Village. It is expected that through the system, the reporting of realization of PBB revenue in all villages in Banyuwangi becomes more optimal and created more effective and efficient performance.